Parable of the sower : a graphic novel adaptation - Duffy, Damian (Butler, Octavia E. Earthseed books., 2020)
In this graphic novel adaptation of Octavia E. Butler's Parable of the Sower, by Damian Duffy and John Jennings, the award-winning team behind the #1 bestseller Kindred: A Graphic Novel Adaptation, the author portrays a searing vision of America's future. In the year 2024, the country is marred by unattended environmental and economic crises that lead to social chaos. Lauren Olamina, a preacher's daughter living in Los Angeles, is protected from danger by the walls of her gated community. However, in a night of fire and death, what begins as a fight for survival soon leads to something much more: a startling vision of human destiny . . . and the birth of a new faith.